Predictors of Quality of Life in Patients With Myocardial Infarction Combined With Dyslipidemia - Zhang, Mengran; Chen, Pingyu; Zhang, Yan; Su, Xi; Chen, Jiyan; Xu, Biao; Tao, Jianhong; Wang, Zhen; Li, Hongchao; Ma, Aixia (Frontiers in Public Health, 2021)
Background: Dyslipidemia is an important risk factor for myocardial infarction (MI). This study aimed to examine the health-related quality of life (HRQoL) and its predictors of patients with MI combined with dyslipidemia in China. Methods: Information on patients' sociological characteristics, lifestyle, clinical characteristics, and quality of life were collected by electronic medical records and questionnaires. Tobit regression model was used to investigate the predictors of quality of life. Results: There were 756 patients responded. The average EQ-5D score of all the patients was 0.95 (SD: 0.11). For all patients, factors such as age, high-fat and high-cholesterol diet, sports, family history of dyslipidemia, history of peripheral artery disease significantly affected HRQoL. Conclusions: Post-discharge care of the elderly group should be paid more attention to and suggestions on the healthy lifestyle (fat control) of the patients should be encouraged to improve the quality of life of these population.